Exchange rates and the volume of trade—The case for fixed exchange rates - Christa Randzio-Plath (Intereconomics, 1994)
Exchange rate volatility and long-term distortions of exchange rate levels have given rise to concern among participants in international trade. Do exchange rate fluctuations have an adverse impact on the volume of trade? What measures could be taken to achieve greater exchange rate stability?
Keywords: 330; Monetary Policy